2001
DOI: 10.1093/humrep/16.7.1420
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anxiety and depression on the outcome of in-vitro fertilization

Abstract: Pre-existing psychological factors are independently related to treatment outcome in IVF/ICSI, and should therefore be taken into account in patient counselling. Psychological factors may be improved by intervention, whereas demographic and gynaecological factors cannot. Future studies should be directed towards underlying mechanisms involved and the role of evidence-based distress reduction in order to improve treatment results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
114
3
14

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(147 citation statements)
references
References 24 publications
16
114
3
14
Order By: Relevance
“…The literature in western countries shows that psychosocial interventions can have beneficial effects on biological responses and/or increase pregnancy rates after IVF (30,31). In the EBMS intervention program, the pregnancy rate is not the primary target; rather, the therapeutic focus is spiritual transformation, enabling the woman to reconstruct her meaning of life by relinquishing her attachment to the concept of the "children-focused ideal family.…”
Section: Assumptions and Therapeutic Goals Of The Eastern Body-mind-smentioning
confidence: 99%
“…The literature in western countries shows that psychosocial interventions can have beneficial effects on biological responses and/or increase pregnancy rates after IVF (30,31). In the EBMS intervention program, the pregnancy rate is not the primary target; rather, the therapeutic focus is spiritual transformation, enabling the woman to reconstruct her meaning of life by relinquishing her attachment to the concept of the "children-focused ideal family.…”
Section: Assumptions and Therapeutic Goals Of The Eastern Body-mind-smentioning
confidence: 99%
“…Evidence showed that ≅34%-47% of fertility treatment patients are at risk of maladjustment (Lopes et al, 2014;Verhaak et al, 2010), who sometimes feel embarrassed seeking help and support (Hanna and Gough, 2016). While measures of general psychological adjustment (e.g., anxiety, depression) have been used initially to assess the impact associated with this challenge (Emery et al, 2003;Salvatore et al, 2001;Slade et al, 1997;Smeenk et al, 2001), some authors claimed that the use of general psychological instruments may not capture the specific experience of infertility (Boivin, 2003;Greil et al, 2016;Schmidt, 2009). This has stimulated the development of more than 10 self-report measures assessing infertility psychosocial adjustment (see reviews of Gourounti et al, 2010;Martins et al, 2016), the most used being the COMPI Fertility Problem Stress Scales (COMPI-FPSS, Schmidt, 2006;, the Fertility Problem Inventory (FPI, Newton et al, 1999) and the Fertility Quality of Life Tool (FertiQoL, Boivin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have examined stress and mood states as predictors of outcome in assisted reproduction. The majority of these support the theory that emotional distress (as defined above, tension, nervousness or worry not fulfilling criteria for a diagnosis of depression or anxiety disorder) is associated with lower pregnancy rates among women pursuing infertility treatment (Sanders 1999;Smeenk 2001).…”
Section: Influence Of Psychological State On Treatment Outcomementioning
confidence: 67%
“…A number of studies have found that the incidence of depression in infertile couples presenting for infertility treatment is significantly higher than in fertile controls, with prevalence estimates of major depression in the range of 15-54% (Downey 1989;Fassino 2002;Chen 2004). It is important to evaluate women at the beginning of their infertility diagnosis and treatment, as most studies have shown that the presence of depressive symptoms is associated with longer duration of treatment (Thiering 1993;Kee 2000;Smeenk 2001;Lok 2002).…”
Section: Anxiety and Depressionmentioning
confidence: 99%
See 1 more Smart Citation